Sustainable After Sale Services: The Effect of Perceived Value on Customers’ Behavioural Intention - Gupta, Rajni; R, Sreedhara (International Journal of Psychosocial Rehabilitation, 2020)
It is believed that in the coming future the most important factor in any industry will no longer be technology or capital, but the environment (Sheth & Sinha, 2015). This clearly shows the main concern for any industry from any part of the world and also shows their concern towards future generations. To make sure that any action taken today does not limit the socio-economic and environmental choices to the future generation, the fundamental principle of sustainability has arisen (Trevena, Kaldor & Downs, 2014). Seeing the trend, Recently, the service industry has also started focusing on sustainability management. Green after-sale services in consumer durables have become an integral part of the service industry. Customer support determines sustainable development by endorsing sustainable operations and their services. Different customers perceive different values from sustainable services, leading to their behavioral intentions. Therefore, the aim of this paper is to examine the relationship between perceived values, i.e., hedonic and utilitarian principles, and customer’s behavioral expectations. A total of 360 relevant questionnaires were obtained and regression was used to assess and check the hypotheses of the research. The study provides empirical evidence of effect of hedonic and utilitarian principles on the actions of customers. Finally, managerial implications are discussed, and propositions are made for the future.